Peran Bimbingan Konseling Islam dalam Meminimalisasi Bullying antar Teman di Lingkungan Sekolah - Nilasari, Susi; Prahastiwi, Eka Danik (Lembaga Yasin AlSys, 2023)
Bullying is a desire to hurt, which is shown into action and causes someone to suffer. Cases of bullying, especially those perpetrated by children and adolescents in the school environment, are still very high. This is evidenced by data from the Indonesian Child Protection Commission (KPAI) regarding cases of bullying in 2023 which are increasing. In Islam bullying behavior is strictly prohibited and not recommended because it is included in the behavior of demeaning others. One way that can be used to prevent and minimize bullying is the application of Islamic Counseling Guidance. The aim of this research is to find out the role of Islamic Counseling Guidance in minimizing bullying behavior including, what methods are used and how effective or successful it is. This study uses a qualitative approach. The type of research used is library research with the documentation method, namely finding and studying data regarding variables in the form of notes, documents, books, journals and so on. The data sources used are primary and secondary data sources. The data analysis technique used is content analysis method. To test the validity of this research data using a credibility test by increasing persistence, researchers also use source triangulation techniques. Islamic Counseling Guidance has many methods or ways as efforts that can be applied in preventing and minimizing acts of bullying in accordance with the needs of students. Thus, making students show changes in attitudes and behavior in a more positive direction. This indicates that Islamic Counseling is a successful and effective way to minimize acts of bullying between friends at school.